Happy town: Cultural governance and biopolitical urbanism in China. (February 2019) - Oakes, Tim
This paper explores the cultural inscription of urban space in China as a technology of government. Based on a three years of fieldwork, including interviews, surveys, and participant observation, the paper examines the case of one city's campaign to increase its "happiness index" by creating an ethnic culturally themed built environment. The paper examines the city's happiness campaign as a project of biopolitical urbanism, and finds that while urban Chinese governmentality bears some striking resemblances to liberal approaches that view the city as a machine for experimenting with, and producing, certain kinds of (governable) citizens and social relations, the happiness campaign should also be understood as a deliberate effort to reinforce state power at the local level. The happiness campaign, in other words, aims to reproduce a sovereign mode of state power even as it speaks a language of neoliberal governmentality. Thus, the colonization of culture by biopolitical urbanism in China today suggests a complex combination of disciplinary and discursive modalities of sovereign power rooted in the paternalistic legacies of Chinese statecraft.